Study of Base Shear and Inter-Story Drift due to Earthquake Forces on a Ten-Story Building Structure in Surakarta - Assidiq, Yudistira Cahaya; Bali, Ika (President University, 2025)
Earthquakes are the frequent natural disasters that hit Indonesia as a consequence of the country's geographical location. Surakarta City become a region that frequently suffers the effects of earthquakes. Earthquake disasters threaten high-rise building structures in Surakarta City, where earthquake loads acting on the structure can cause damage and even structural collapse. These historical and geographical reasons become the foundation of this research to analyze high-rise building structures in Surakarta City. In this study, the structural conditions of the analyzed high-rise buildings comply with the equivalent static method's analysis requirements, so that this method can be employed in this research. The equivalent static analysis was conducted through manual calculation and the ETABS program. This study focuses on several structural parameters, including base shear force, and inter-story drift. Based on the analysis that was already conducted, the base shear force was obtained at 14392.365 kN through manual calculation and 14984.490 kN through ETABS program analysis. The inter-story drift value that was already calculated fulfils the maximum threshold requirements, where the inter-story drift values are 17.984 mm – 68.183 mm in the X direction and 9.846 mm - 46.804 mm in the Y direction.